2018
DOI: 10.1038/s41568-018-0005-8
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the role of ABC transporters in multidrug-resistant cancer

Abstract: Most patients who die of cancer have disseminated disease that has become resistant to multiple therapeutic modalities. Ample evidence suggests that the expression of ATP-binding cassette (ABC) transporters, especially the multidrug resistance protein 1 (MDR1, also known as P-glycoprotein or P-gp), which is encoded by ABC subfamily B member 1 (ABCB1), can confer resistance to cytotoxic and targeted chemotherapy. However, the development of MDR1 as a therapeutic target has been unsuccessful. At the time of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
1,254
1
13

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,328 publications
(1,392 citation statements)
references
References 160 publications
6
1,254
1
13
Order By: Relevance
“…Also on protein level, lower expression levels in ccRCC tissues were linked to inferior survival. 12 However, similar to BCRP/ABCG2, we found that decreased expression of MDR1/ABCB1 is associated with poor patient survival in ccRCC. For instance, the lactate transporter MCT4 is overexpressed in ccRCC and high MCT4 expression is linked to poor patient survival.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Also on protein level, lower expression levels in ccRCC tissues were linked to inferior survival. 12 However, similar to BCRP/ABCG2, we found that decreased expression of MDR1/ABCB1 is associated with poor patient survival in ccRCC. For instance, the lactate transporter MCT4 is overexpressed in ccRCC and high MCT4 expression is linked to poor patient survival.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, due to a potential compensatory role because of functional redundancy, 12 we evaluated the multidrug resistance protein MDR1/ABCB1 expression and its association with patient survival. Moreover, due to a potential compensatory role because of functional redundancy, 12 we evaluated the multidrug resistance protein MDR1/ABCB1 expression and its association with patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…P-gp transports one molecule of the substrate across the membrane, requiring two molecules of ATP to provide energy [37]. If the energy supply is insufficient, the function of P-gp is inhibited [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The basic structure of P-gp contains four core active regions, namely two hydrophilic nucleotide-binding domains (NBD) located in the cytoplasm that are responsible for binding to ATP and two hydrophobic transmembrane domains (TMD) that are responsible for binding to the substrate for P-gp transport [37,41]. For 4M2T, a corrected structure of mouse P-gp bound to QZ59-SSS, the corrected position of TMD4, which forms the frame of a portal for drug entry.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is usually used in the treatment of gastric cancer both in adjuvant and advanced settings [4]. Although chemotherapy has improved the survival of patients with gastric cancer, the development of multidrug resistance (MDR) is still a crucial problem leading to therapeutic failure and cancer-related death [5]. In addition, the underlying molecular mechanisms of MDR in gastric cancer remain elusive.…”
Section: Introductionmentioning
confidence: 99%